Investment behaviour : towards an individual-centred financial policy in developing economies - Kumar Sarkar, Arup; Sahu, Tarak Nath, 1982- (Emerald Publishing Limited, 2018)
'Investment Behaviour' explores the relationship between competing demographic factors, personal awareness and perceived attitudes to risk in shaping the behaviour of individual investors in the stock market. Arup Kumar Sarkar and Tarak Nath Sahu analyse the suitability of using Behavioural Finance theories in understanding investor behaviour across developed, developing and under-developed country contexts and in all types of stock markets. Across an in-depth study, the authors examine differing variables impacting on behaviour, give an overview of the empirical and theoretical literature, and also provide an analysis of the empirical findings of their investigation. The book promotes a greater understanding the psychological foundations of human behaviour in financial markets to facilitate the formulation of more individual-centered financial policy.
Includes index.
Keywords: Investments -- Mathematical models.; Capital investments -- India -- Simla (District); Individual investors.; Stock exchanges.; Business & Economics, Investments & Securities, Portfolio Management.; Investment & securities.; elektronické knihy; electronic books